(untitled) (Research, Society and Development, 2020)
Much of the construction and demolition waste in the municipality of Belém is generated by large companies. The National Plan for Solid Waste aims to minimize such waste, as well as to reduce expenses with its treatments and final destination, thus benefiting companies, considering a lower cost and better production. The countries’ economic growth is accompanied by the expansion of the construction industry; and one of the consequences of this phenomenon is the generation of major environmental impacts, from the extraction of natural resources for the production of inputs, to the production of waste, which is disposed of in the environment without adequate control and management. This study deals with civil construction and demolition waste generated by large companies in the city of Belém, Pará. The objective was to quantify, classify, and present the main problems caused by this waste, with a private company as the object of research. Firstly, data were collected to conduct the research, consulting the collection made available by the Municipality of Belém, the Department of Sanitation and the National Environment Council. Subsequently, questionnaires and interviews were also developed and applied to make the results possible. The data collected in civil construction projects in the metropolitan region of Belém showed a gap in terms of theory and practice in the proper disposal of waste and tailings. Although there is knowledge of the regulations that regulate this process, construction companies do not follow the standardized standards.